PENTINGNYA NEW STRATEGI PENGELOLAAN KEUANGAN BAGI PERUSAHAAN YANG SEMPAT MENGALAMI KEBANGKRUTAN - Fitriyana, Mifta (Journal Competency of Business, 2023)
A business owner will continue to try to manage the business so that it does not lose, no matter how difficult the situation is. Going concern is what is desired. Companies experience growth from one stage to another so as to form a company life cycle. This indicates that every process in the company's life has its own challenges that need to be managed with the best possible effort. When a company is unable to overcome the problems that exist in certain phases, there is a possibility that the company will go bankrupt or be liquidated. One of them is a new financial management strategy that must be implemented. Financial management in a business is very basic if the finances in the company want to be healthy or not. With this new financial management strategy, it is hoped that there will be a new gap of hope for the company to save its business, although not only that, but it also requires saving from other aspects such as the overall strategy.